1997
DOI: 10.1037/0022-006x.65.5.740
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the therapeutic focus in cognitive–behavioral and psychodynamic–interpersonal sessions.

Abstract: This study compared therapeutic foci in a sampling of 30 cognitive-behavioral and 27 psychodynamic-interpersonal manual-driven treatments for depression. High-and low-impact sessions were coded for each client, with the Coding System of Therapeutic Focus. Results indicated that psychodynamic-interpersonal sessions focused more on such variables as emotion, patterns, incongruities, the impact that others made on clients, clients' expected reaction of others, the tendency to avoid therapeutic progress, therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 23 publications
6
72
2
6
Order By: Relevance
“…Qualitative comparison of the treatment profiles is consistent with research documenting similarities and differences in standard technical interventions (e.g., reflection, interpretation, advisement, and so on) associated with CBT versus PI therapy (Goldfried et al, 1997;Stiles & Shapiro, 1995;Wiser & Goldfried, 1996). In past studies, as in the present comparison, clear-cut distinctions between "brands" of treatment are often difficult to make based solely on empirical process variables.…”
Section: Patterns Of Interpersonal Behavior For Cognitive-behavioral supporting
confidence: 50%
See 1 more Smart Citation
“…Qualitative comparison of the treatment profiles is consistent with research documenting similarities and differences in standard technical interventions (e.g., reflection, interpretation, advisement, and so on) associated with CBT versus PI therapy (Goldfried et al, 1997;Stiles & Shapiro, 1995;Wiser & Goldfried, 1996). In past studies, as in the present comparison, clear-cut distinctions between "brands" of treatment are often difficult to make based solely on empirical process variables.…”
Section: Patterns Of Interpersonal Behavior For Cognitive-behavioral supporting
confidence: 50%
“…Although previous research provides us with this prediction regarding hostile behaviors in general, results have not been entirely uniform in terms of specific SASB clusters. In addition, differences have been documented between typical verbal interventions used in psychodynamic and cognitive-behavioral therapies suggesting that different interpersonal stances may be associated with these two general treatment approaches (Goldfried, Castonguay, Hayes, Drozd, & Shapiro, 1997;Stiles & Shapiro, 1995;Wiser & Goldfried, 1996). Furthermore, Bordin (1979) has suggested that different kinds of client-therapist alliances (and, by implication, interpersonal processes) may be predictive of outcome in different therapies.…”
Section: Cognitive-behavioral Therapy Interpersonal Process and Outmentioning
confidence: 93%
“…In comparative process studies that examined the differences between cognitive‐behavior therapy and psychodynamic‐interpersonal therapy, our own research group came up with findings that bear on this discrepancy between research and practice. In analyzing manual‐driven therapy sessions conducted within the context of a controlled clinical trial, we found clear, theoretically consistent differences between the two orientations, with few differences between high‐ and low‐impact sessions (Goldfried, Castonguay, Hayes, Drozd, & Shapiro, 1997). However, different findings emerged with a comparable process analysis involving master therapists working within a naturalistic setting, each of whom had been nominated by experts as a person from their own orientation to whom they would refer a friend or relative (Goldfried, Raue, & Castonguay, 1998).…”
Section: Whom Do We Believe: Scientist or Practitioner?mentioning
confidence: 93%
“…For example, PIT has a greater focus on within session experiences and the client's past and current relationships and emotional issues compared to CBT that tends to focus on external situations and the future (Goldfried, Castonguay, Hayes, Drozd, & Shapiro, 1997). …”
Section: Process Researchmentioning
confidence: 98%